Reversal of Anomalous Hall Effect and Octahedral Tilting in SrRuO3 Thin Films via Hydrogen Spillover. Issue 3 (20th November 2022) - Han, Hyeon; Zhou, Hua; Guillemard, Charles; Valvidares, Manuel; Sharma, Arpit; Li, Yan; Sharma, Ankit K.; Kostanovskiy, Ilya; Ernst, Arthur; Parkin, Stuart S. P.
Abstract: The perovskite SrRuO3 (SRO) is a strongly correlated oxide whose physical and structural properties are strongly intertwined. Notably, SRO is an itinerant ferromagnet that exhibits a large anomalous Hall effect (AHE) whose sign can be readily modified. Here, a hydrogen spillover method is used to tailor the properties of SRO thin films via hydrogen incorporation. It is found that the magnetization and Curie temperature of the films are strongly reduced and, at the same time, the structure evolves from an orthorhombic to a tetragonal phase as the hydrogen content is increased up to ≈0.9 H per SRO formula unit. The structural phase transition is shown, via in situ crystal truncation rod measurements, to be related to tilting of the RuO6 octahedral units. The significant changes observed in magnetization are shown, via density functional theory (DFT), to be a consequence of shifts in the Fermi level. The reported findings provide new insights into the physical properties of SRO via tailoring its lattice symmetry and emergent physical phenomena via the hydrogen spillover technique. Abstract : The perovskite SrRuO3 is a prototypical itinerant ferromagnet that has drawn considerable attention due to its strongly correlated physical properties. In this work, a new concept is demonstrated to induce octahedral distortions, magnetism, and reversal of the anomalous Hall effect in SrRuO3 thin films via hydrogen spillover, revealed by comprehensive in situ experiments and density functional theory calculations.